Tantangan Etika Di Era Digital Banking Dan Financial Technology: Implikasi Terhadap Kepercayaan Nasabah Dan Keberlanjutan Industri Perbankan - Muhammad Irfan; Rudi Sanjaya; Raehan Ali; Muhammad Inayatulla; Egie Fahrizal; Aditya Pratama (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The rapid development of Financial Technology (FinTech) and Digital Banking has transformed the financial services industry by providing more efficient, accessible, and innovative services. However, the increasing dependence on digital technology has raised various ethical challenges related to data privacy, cybersecurity, transparency, accountability, and consumer protection. This study aims to analyze ethical issues arising in digital banking and financial technology and examine their implications for customer trust and the sustainability of financial institutions. The research employs a qualitative approach through a literature review of scientific journals, books, regulations, and official reports published between 2019 and 2025. The findings reveal that data misuse, cyber threats, algorithmic bias, and inadequate disclosure of digital financial services remain significant ethical concerns. Furthermore, ethical governance plays a crucial role in maintaining customer trust and institutional reputation. The study concludes that technological innovation must be accompanied by strong ethical frameworks, regulatory compliance, and responsible digital governance to ensure sustainable growth in the digital financial ecosystem.